Alcohol-Attributable Fraction in Liver Disease: Does GDP Per Capita Matter? - Paul T. Kröner (Annals of Global Health, 2016)
Background: The alcohol-attributable fraction (AAF) quantifies alcohol's disease burden. Alcoholic liver disease (ALD) is influenced by alcohol consumption per capita, duration, gender, ethnicity, and other comorbidities. In this study, we investigated the association between AAF/alcohol-related liver mortality and alcohol consumption per capita, while stratifying to per-capita gross domestic product (GDP). Methods: Data obtained from the World Health Organization and World Bank for both genders on AAF on liver disease, per-capita alcohol consumption (L/y), and per-capita GDP (USD/y) were used to conduct a cross-sectional study. Countries were classified as “high-income” and “very low income” if their respective per-capita GDP was greater than $30,000 or less than $1,000. Differences in total alcohol consumption per capita and AAF were calculated using a 2-sample 't' test. Scatterplots were generated to supplement the Pearson correlation coefficients, and F test was conducted to assess for differences in variance of ALD between high-income and very low income countries. Findings: Twenty-six and 27 countries met the criteria for high-income and very low income countries, respectively. Alcohol consumption per capita was higher in high-income countries. AAF and alcohol consumption per capita for both genders in high-income and very low income countries had a positive correlation. The F test yielded an F value of 1.44 with 'P' = .357. No statistically significant correlation was found among alcohol types and AAF. Significantly higher mortality from ALD was found in very low income countries relative to high-income countries. Discussion: Previous studies had noted a decreased AAF in low-income countries as compared to higher-income countries. However, the non-statistically significant difference between AAF variances of low-income and high-income countries was found by this study. A possible explanation is that both high-income and low-income populations will consume sufficient amount of alcohol, irrespective of its type, enough to weigh into equivalent AAF. Conclusions: No significant difference of AAF variance was found between high-income and very low income countries relating to sex-specific alcohol consumption per capita. Alcohol consumption per capita was greater in high-income countries. Type of preferred alcohol did not correlate with AAF. ALD related mortality was less in high-income countries as a result of better developed healthcare systems. ALD remains a significant burden globally, requiring prevention from socioeconomic, medical, and political realms.